Proposed neural crest involvement in concomitant bifid xiphoid process and atrial septal defect: A case study and review of literature - Adam Pasquinelly; Hamoun Delaviz; Adel Maklad; Patrick William Frank (Elsevier, 2022)
Background: The sternum and the heart are derived from the mesodermal germ layer; abnormalities in their development and differentiation can result in sternal and cardiac defects, including bony malformations and septal defects, respectively. The shape and size of xiphoid process congenital anomalies vary greatly among available literature. However, one notable study has reported a nearly identical presentation to this case, both in xiphoid morphology and presence of a patent foramen ovale. Given that the two structures have a common mesodermal origin with suspected neural crest involvement, further investigation into the possibility of a shared etiology may be warranted. Case Report: We present a case of patent foramen ovale and bifid xiphoid process discovered during routine educational dissection of a 90-year-old Caucasian female cadaver. Discussion: While sternal morphological variation is common, its concurrence with an atrial septal defect is not well documented outside of certain congenital syndromes, and points to abnormalities of a common developmental origin - the neural crest. The heart is known to have neural crest contributions to its development, and neural crest involvement in sternal development has been theorized as well. Available literature describes several neurocristopathies and other congenital syndromes presenting with both sternal and cardiac involvement, though exact neural crest participation in the development of each region is not fully understood. Conclusion: This case prompts a closer look into neural crest contributions to both the heart and sternum. A link between sternal and cardiac defects could provide evidence for cardiac abnormality screenings in high-risk patients with incidentally discovered sternal abnormalities.